Pengaruh Layanan Deteksi Transaksi E-Commerce Nirlaba dalam Hal Dampaknya Terhadap Instrumen Kebijakan Moneter Islam - Lely Mawaddah; Muhammad Lathief Ilhamy Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Abstract The researcher uses a qualitative approach method and through field studies and also based on several previous journals. The study population consisted of several buyers affected by gharar after buying and selling online applications such as Shopee, Lazada and Tokopedia. The results of this study were obtained after the researcher interviewed directly with buyers affected by gharar. The practice of gharar used by sellers is to describe the products they sell well without explaining the defects or badness of the products they sell. Directly or indirectly, such business practices undermine or weaken the company's competitive power. Basically, transparency and honesty are the most important things in trading activities.